A geopolitical look at Science and Technology: global tensions and imaginaries. The case of bioinputs in argentina - Macedo, María Guadalupe (SCT Proceedings in Interdisciplinary Insights and Innovations, 2024)
Bioinputs constitute a new technological promise that opens the possibility of reconciling opposing interests within the agricultural field, which must be thought in the global context where multiple factors such as political, cultural, social, economic and legal influence. The following work had the objective of establishing a geopolitical view on the situation of bioinputs in Argentina and the link between world order, foreign policy and technological development.This work was framed within science and technology studies from a critical communication theory perspective. We start from the following research question: Would technological autonomy in agricultural bioinputs allow the consolidation of national sovereignty? Is the development of bioinputs in the country a promise for the development of the country to move from being a peripheral country to a central country? It is intended to look at how the case of technological innovations of bioinputs play a central role in terms of scientific and technological development from a geopolitical point of view, having as an axis to articulate the concept of socio-technical imaginary. Based on a case study: bioinputs in Argentina, it was intended to analyze the discursive genres taking into account the discourse analysis proposed by Van Dijk (1996), analyzing the structures and functions of the text in its social, political and cultural context from the viewpoint of critical thinking